Tuesday

March 31, 2015

March 31, 2015

Posted by **Shane** on Sunday, September 1, 2013 at 2:01am.

- maths -
**Graham**, Sunday, September 1, 2013 at 2:15amRearrange into incomplete quadratics:

(x² + 2x) + (y² - 2y) = 1

Complete the squares:

(x² + 2x + 1) + (y² - 2y + 1) = 1 + 1 + 1

Express in the required form:

(x + 1)² + (y - 1)² = (√3)²

Thus: h = -1, k = 1, r = √3

**Answer this Question**

**Related Questions**

maths - A circle x^2 + y^ + 2x - 2y -1 = 0 expressed in the following form (x-h...

maths - the circle is given by the equation x^2+y^2+8x-7/2y=0 find (i)...

Maths - In an orthonormal system, you're given the following: Point P(1,2) Lina ...

maths - 1) Circle centre (7,-2) passes through (-2,10). Calculate radius and ...

Maths again - For the transformation w=z^2, show that as z moves once round the ...

maths - given the following equation for a circle x^2-8x+y^2+4y+11=0 find its ...

Maths - In polar coordinates, the parametric equations x=6+cos(f) and y=sin(f) ...

Mathematics - In an orthonormal system, you're given the following: Point P(1,2...

maths - Given that the equation of the circle is x^2+y^2+2x-8y+5=0 (i)find the ...

maths - Given that the equation of the circle is x^2 + y^2 +2x -8y+5 =0 (i)Find ...